2021
DOI: 10.1002/cpp.2607
|View full text |Cite
|
Sign up to set email alerts
|

Moral injury, mental health and behavioural health outcomes: A systematic review of the literature

Abstract: Despite a burgeoning of research on moral injury in the past decade, existing reviews have not explored the breadth of consequences and the multitude of pathways through which moral injury and potentially morally injurious experiences (PMIEs) influence mental and behavioural health outcomes. This study aimed to identify associations between moral injury on mental and behavioural health. Literature searches of psychological and medical databases were conducted through April 2020. Eligible studies measured moral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 119 publications
(285 reference statements)
9
77
0
Order By: Relevance
“…As hypothesized and similar to previous findings [ 21 ], we found that MI was related to burnout. We also found that MI was associated with higher levels of psychiatric symptoms including depression, anxiety, and PTSD, a finding that is consistent with prior research focused on HCPs [ 3 , 15 ] and military samples [ 42 ]. In our sample, providers who reported Others MI were almost three times more likely to score above the clinical cutoff for depression, while those reporting Self MI were over two times more likely to score above the clinical cutoff for depression, over four times more likely to score above the clinical cutoff for anxiety, and over 6 times more likely to score above the clinical cutoff for PTSD.…”
Section: Discussionsupporting
confidence: 90%
“…As hypothesized and similar to previous findings [ 21 ], we found that MI was related to burnout. We also found that MI was associated with higher levels of psychiatric symptoms including depression, anxiety, and PTSD, a finding that is consistent with prior research focused on HCPs [ 3 , 15 ] and military samples [ 42 ]. In our sample, providers who reported Others MI were almost three times more likely to score above the clinical cutoff for depression, while those reporting Self MI were over two times more likely to score above the clinical cutoff for depression, over four times more likely to score above the clinical cutoff for anxiety, and over 6 times more likely to score above the clinical cutoff for PTSD.…”
Section: Discussionsupporting
confidence: 90%
“…This study found that over one-third of the health professionals reported suffering signi cant MI symptoms. Studies have found that MI has been associated with several adverse mental health outcomes and lower quality of health care (including increased medical errors) [32]. The prevalence in the study post-pandemic is lower than in a study conducted during the early stage of the pandemic when healthcare resources were extremely limited and the number of positive cases increasing rapidly [33].…”
Section: Discussionmentioning
confidence: 79%
“…This result shows the need for institutional meddling to prevent emotions such as overwhelm, fear, frustration and feelings of hopelessness, and helplessness. Since these emotions and feelings are associated with significant mental health challenges such as mental illnesses, behavioral issues (e.g., substance misuse), physical health challenges (e.g., sleep disturbances), and occupational impairment (e.g., burn-out and work absenteeism) ( 30 ).…”
Section: Discussionmentioning
confidence: 99%